Projections overview and highlights, 2019--29. - Dubina, Kevin S.; Kim, Janie-Lynn; Rolen, Emily; Rieley, Michael J. (Monthly Labor Review, 2020)
Employment and real output growth are projected to slow from 2019 to 2029. One in four people will be ages 65 and older in 2029, contributing to slower projected growth in the labor force and a continued decline in the labor force participation rate. The aging population is expected to continue to drive strong demand for a variety of healthcare services, with 3.1 million jobs projected to be added in the healthcare and social assistance sector through 2029.